Character Development of Bryce Loski & Juli Baker in ‘Flipped’ Movie - Apriyanti , Fitri (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2022)
In literary works, specifically movies, a character is one of the important elements. The development of this character is also important in supporting the storyline in a movie. Character development can be influenced by many factors. Therefore, this paper aims to find out what factors influence the character development and how these factors influence the character development of the main character in the movie. This study uses a qualitative method with sources from the original Flipped video and uses data collection techniques from online sources using the theory of family pattern of interactions by Guralnick. The results of this study indicate that: (1) 12 data indicate the factor that influences the character development of Bryce Loski and Juli Baker, the main character of the Flipped movie, is the family interaction factor. (2) Character development of Bryce Loski and Juli Baker is influenced through Parent-Child Transactions, Family-Orchestrated Child Experiences, and Health and Safety Provided by Family